Immaginazione creatrice: dal primitivo al simbolico nella riflessione di Ernst Cassirer - Randazzo, Ivana (Aesthetica Preprint, 2023)
Far from downplaying the role of reason, Ernst Cassirer focuses on the deepest root by which human being is to be regarded not only at biological level as an organism but also as a cultural subject endowed with the power to shape its own world. A key function in every cultural manifestation is played by imagination, which provides the primitive energy in the spiritual effort of making into a symbolic reality what occurs in the human horizon. Like his friend and colleague Aby Warburg, Cassirer begins by shedding light on the mythological imagination in order to investigate the polarity between logical reasoning and irrational attitude within which the whole creative process of symbolization takes place. In this way, imagination is understood as the primary human force from which the process of abstraction that characterizes human experience develops.